2016
DOI: 10.1039/c5em00540j
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of naturally-occurring radionuclides (NORM) in Marcellus Shale produced fluids influenced by chemical matrix

Abstract: Naturally-occurring radioactive materials (NORM) associated with unconventional drilling produced fluids from the Marcellus Shale have raised environmental concerns. However, few investigations into the fundamental chemistry of NORM in Marcellus Shale produced fluids have been performed. Thus, we performed radiochemical experiments with Marcellus Shale produced fluids to understand the partitioning behavior of major radioelements of environmental health concern (uranium (U), thorium (Th), radium (Ra), lead (Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Therefore, decontamination can be carried out using methods that combine a high degree of mechanization of all technological operations, remote control of processes and reliable localization of radionuclides to a limited extent [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, decontamination can be carried out using methods that combine a high degree of mechanization of all technological operations, remote control of processes and reliable localization of radionuclides to a limited extent [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…While 72 Ga is recognized as an acceptable radionuclide for application of the isotope dilution approach, there is no commercial manufacturer and a reactor with high neutron flux irradiation capabilities is required for preparation of 72 Ga standards. 52 On the other hand, multiple manufacturers of 68 Ga generators are emerging and the availability of 68 Ga continues to 29 increase. 19 Further, the half-life of 68 Ga (68 m The use of 68 Ga as a radioisotopic tracer for the determination of stable Ga is desirable because the positron emission provides easily measured 511 keV gamma rays for direct measurement by ion chamber.…”
Section: Resultsmentioning
confidence: 99%
“…28 The problem with Ba for radiochemical separations is that Ba and Ra have very similar chemistry and often co-elute or co-precipitate during chemical separations. [28][29][30][31] The high levels of dissolved solids (in particular the high concentrations of Ba) suggested that a low-cost, rapid, practical separation of Ra from the Marcellus Shale fluids would not be possible. Given that Ra had been previously established as a key radionuclide in Marcellus Shale produced fluids and flowback, 21,32 this suggested that a single gross alpha/beta method was impractical.…”
Section: Methods Developmentmentioning
confidence: 99%
See 2 more Smart Citations